PERANCANGAN APLIKASI WAREHOUSE MANAGEMENT DENGAN PENDEKATAN METODE FUZZY MAMDANI - Edy Nasri; Kornelis Kornelis; Hambali Syamsuddin (Jurnal Ilmiah Sains dan Teknologi, 2022)
Company PT. Loyal Indonesia Utama, is engaged in the production of switches, sockets, sockets, plugs and cable boxes located in Serang Regency, there are some parts of the data collection process that still use the speedsheet application and some are still recorded using a manual form. The problems found in this research are in the warehouse section where there is still inappropriate production planning, delivery of goods and receipt of goods is not scheduled and recorded properly, discrepancies between stock and physical data are found. To increase the accuracy and precision in the calculation of goods, one of which is the support of technology and information systems according to needs. Where data can be processed and processed so as to produce information to support good decisions, this research offers a solution by designing a Warehouse Management system application where the application development uses the RAD method, system development modeling used is the Unified Modeling Language, in making this software using the PHP programming language with the CodeIgniter Framework and for data storage using MySQL DBMS which is used to create application, The method for solving problems in the research used is Fuzzy Mamdani (Min-Max) to determine the amount that must be available in the warehouse.